Coronary surgery with non-cardioplegic methods in patients with advanced left ventricular dysfunction: immediate and long term results - Antunes, PE (2008)
OBJECTIVE: To evaluate perioperative results and long term survival in patients with severe left ventricular (LV) dysfunction undergoing coronary artery bypass grafting (CABG) using non-cardioplegic methods. METHODS: From April 1990 through December 1999, 4100 consecutive patients underwent isolated CABG using hypothermic ventricular fibrillation. Of these, 141 (3.4%) had severe LV dysfunction (ejection fraction < 30%). Mean age was 58.3 (9.6) years. 64 patients (45.4%) were in Canadian Cardiovascular Society class III or IV and 16 (11.3%) were subjected to urgent or emergent surgery. A previous myocardial infarction was recorded in 127 (90.1%). The majority (89.4%) had triple vessel and 26 (18.4%) had left main disease. The mean number of grafts per patient was 3.1. At least one internal thoracic artery was used in all patients and 21 (14.8%) had bilateral internal thoracic artery grafts (1.2 arterial grafts per patient). RESULTS: Perioperative mortality was 2.8% (4 patients) and the incidence of acute myocardial infarction 2.8%. 50 (35.5%) patients required inotropes but only 16 (11.3%) required it for longer than 24 hours; 5 patients (3.5%) needed mechanical support. The incidence of renal failure was 3.5%. Mean duration of hospital stay was 9.6 (8.3) days. Follow up was 95% complete and extended for a mean of 57 (30) months. Late mortality was 11.5%. Actuarial survival rates at 1, 3, and 5 years were 96%, 91%, and 86%, respectively. CONCLUSIONS: Non-cardioplegic techniques are safe and effective in preserving the myocardium during CABG in patients with coronary artery disease and poor LV function, with low operative mortality and morbidity, and encouraging medium to long term survival rates.